Investigating the attitudes towards euthanasia held by registered nurses enrolled in post-graduate nursing programmes at a university in the Western Cape - Chencinski, Luna (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.